Mapping a gene on wheat chromosome 4BL involved in a complementary interaction with adult plant leaf rust resistance gene LrSV2 - Dieguez, Maria Jose (2018)
A complementary gene to LrSV2 for specific adult plant leaf rust resistance in wheat was mapped on chromosome 4BL, tightly linked to Lr12 / 31. LrSV2 is a race-specific adult plant leaf rust (Puccinia triticina) resistance gene on subdistal chromosome 3BS detected in the cross of the traditional Argentinean wheat (Triticum aestivum) variety Sinvalocho MA and the experimental line Gama6. The analysis of the cross of R46 [recombinant inbred line (RIL) derived from Sinvalocho MA carrying LrSV2 gene and the complementary gene Lrc-SV2 identified in the current paper] and the commercial variety Relmo Siriri (not carrying neither of these two genes) allowed the detection of the unlinked complementary gene Lrc-SV2 because the presence of one dominant allele of both is necessary to express the LrSV2-specific adult plant resistance. Lrc-SV2 was mapped within a 1-cM interval on chromosome 4BL using 100 RILs from the cross Sinvalocho MA × Purple Straw. This genetic system resembles the Lr27+31 seedling resistance reported in the Australian varieties Gatcher and Timgalen where interacting genes map at similar chromosomal positions. However, in high-resolution maps, Lr27 and LrSV2 were already mapped to adjacent intervals on 3BS and Lrc-SV2 map position on 4BL is distal to the reported Lr12/31-flanking microsatellites.